Uterus preservation despite focal placentaaccreta in a patient with multiple previous uterine surgeries: a case report: Ohranitev maternice kljub žariščni prirasli posteljici pri pacientki s številnimi predhodnimi operacijami maternice : prikaz primera - Vidanova, Snezhana; Serdinšek, Tamara; Žebeljan, Ivan; Mujezinović, Faris (Acta Medico-Biotechnica, 2021)
Purpose: More than 50% of the cases of placenta accreta spectrum (PAS), which is defined as abnormal trophoblastic invasion into the uterine myometrium, are prenatally undiagnosed.Despite the increased frequency of PAS in recent years, there is still no consensus regarding its optimal management in the literature. Here, we describe a case of PAS, where a conservative treatment approach was used to preserve a woman’s uterus.Case report: In the third pregnancy of a primiparous woman with multiple previous uterine surgeries, who also had a history of infertility and two missed abortions, a plausible PAS was anticipated despite negative sonographic findings. During elective caesarean delivery, PAS was confirmed, and uterine bleeding was controlled with haemostatic suture placement. The postoperative period was uneventful, and she was discharged on the fourth postoperative day.Conclusion: A high level of suspicion of PAS in patients with predisposing factors but without confirmatory ultrasound findings helps in planning adequate surgical and supportive interventions, thereby reducing postpartum haemorrhage and maternal morbidity.
Keywords: placenta accreta; fertility sparing; haemostatic suturing